Ryan, J.C., Gagliano, M., & Vieira, P. (Eds.). (2021). The Mind of Plants: Narratives of Vegetal Intelligence - Wuyts, Wendy (Journal of Ecohumanism, 2023)
Ryan, J.C., Gagliano, M., & Vieira, P. (Eds.). (2021). The Mind of Plants: Narratives of Vegetal Intelligence. Synergetic Press